Learning to care for the spirit of dying patients: the impact of spiritual care training in a hospice-setting - Wafie Hussein Chahrour; Niels Christian Hvidt; Elisabeth Assing Hvidt; Dorte Toudal Viftrup (BMC Palliative Care, 2021)
Abstract Background Patients approaching the end of their life do not experience their existential and spiritual needs being sufficiently met by the healthcare professionals responsible for their care. Research suggest that this is partly due to a lack of insight about spiritual care among healthcare professionals. By developing, implementing, and evaluating a research-based educational course on spiritual care targeting hospice staff, we aimed to explore the perceived barriers for providing spiritual care within a hospice setting and to evaluate the post-course impact among staff members. Methods Course development and evaluation was based on primary exploratory action research and followed the UK Medical Research Council’s framework for complex intervention research. The course was implemented at two Danish hospices and comprised thematic days that included lectures, reflective exercises and improvised participatory theatre. We investigated the course impact using a questionnaire and focus group interviews. The questionnaire data were summarized in bar charts and analysis of the transcribed interviews was performed based on Interpretative Phenomenological Analysis. Results 85 staff members participated in the course. Of these, 57 answered the evaluative questionnaire and 15 participated in 5 focus group interviews. The course elements that the participants reported to be the most relevant were improvised theatre unfolding existential themes and reflexive group activities. 98% of participants found the course relevant, answering either “relevant” or “very relevant”. 73,1% of participants answered “to a considerable extent” or “to a great extent” when asked to what extent they assessed the content of the course to influence their work in hospice. The focus group data resulted in 3 overall themes regarding perceived barriers for providing spiritual care: 1. Diverse approaches is beneficial for spiritual care, but the lack of a shared and adequate spiritual language is a communicative barrier, 2. Existential conversation is complicated by patients’ overlapping physical and existential needs, as well as miscommunication, and 3. Providing spiritual care requires spiritual self-reflection, self-awareness, introspection, and vulnerability. Conclusions This study provides insights into the barriers facing spiritual care in a hospice setting. Furthermore, the course evaluations demonstrate the valuable impact of spiritual care training for health care professionals. Further course work development is warranted to enhance the “science” of spiritual care for the dying.